2011
DOI: 10.1002/chem.201002942
|View full text |Cite
|
Sign up to set email alerts
|

Broadening Deoxysugar Glycodiversity: Natural and Engineered Transaldolases Unlock a Complementary Substrate Space

Abstract: The majority of prokaryotic drugs are produced in glycosylated form, with the deoxygenation level in the sugar moiety having a profound influence on the drug's bioprofile. Chemical deoxygenation is challenging due to the need for tedious protective group manipulations. For a direct biocatalytic de novo generation of deoxysugars by carboligation, with regiocontrol over deoxygenation sites determined by the choice of enzyme and aldol components, we have investigated the substrate scope of the F178Y mutant of tra… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

4
79
0
3

Year Published

2012
2012
2016
2016

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 57 publications
(86 citation statements)
references
References 101 publications
4
79
0
3
Order By: Relevance
“…Recently, the substrate scope of FSA and TalB F178Y has been investigated with respect to the synthesis of deoxysugars [93]. This study revealed a complementary donor specificity of the two enzymes.…”
Section: Selected Examples For Engineering Of Aldolases and Talsmentioning
confidence: 99%
See 1 more Smart Citation
“…Recently, the substrate scope of FSA and TalB F178Y has been investigated with respect to the synthesis of deoxysugars [93]. This study revealed a complementary donor specificity of the two enzymes.…”
Section: Selected Examples For Engineering Of Aldolases and Talsmentioning
confidence: 99%
“…By a replacement of A129S in FSA, which resembles the TalB active site, the catalytic efficiency towards DHA was greatly improved (17-fold) [94]. The reciprocal substitution in TalB F178Y (TalB F178Y/S176A) resulted in an increased activity for HA [93]. …”
Section: Selected Examples For Engineering Of Aldolases and Talsmentioning
confidence: 99%
“…For both enzymes, the hydroxyacetyl portion in the donor is up to now an absolute structural requirement in either or both Schiff base formation and nucleophile generation [111]. The variable moiety of the donor substrates is accommodated in a highly hydrophobic environment in the binding site of FSA (Leu107, Ala129), whereas polar residues are found in the equivalent positions of TalB (Asn154, Ser176) (Figure 8.7).…”
Section: D-fructose-6-phosphate Aldolase and Transaldolase B Phe178tymentioning
confidence: 99%
“…As mentioned earlier, FSA mutant Ala129Ser, designed to resemble the donor binding site of TalB [107], exhibited improved tolerance toward DHA [6]. In the opposite direction, the poor tolerance of TalB Phe178Tyr toward HA could be partially overcome by substituting the hydrophilic Ser176 for the hydrophobic Ala in the active site (i.e., the double mutant TalB Phe178Tyr/Ser176Ala) (Figure 8.7), the hydrophobic equivalent Ala129 in FSA [111]. The complementary behavior of FSA and TalB mutant was recently exploited to prepare a collection of deoxygenated carbohydrates using FSA for HA and HB aldol additions and TalB Phe178Tyr with DHA (Table 8.4) [6,111].…”
Section: D-fructose-6-phosphate Aldolase and Transaldolase B Phe178tymentioning
confidence: 99%
See 1 more Smart Citation